STUDI LINTAS BUDAYA OPTIMISME PADA MAHASISWA PROGRAM STUDI KEBIDANAN - Musabiq, Sugiarti; Meinarno, Eko Aditiya (Jurnal Psikologi, 2017)
Optimism is a critical aspect influencing midwive candidate in their educational phase because it could affect midwifery students in overcoming any obstacles during their study. One of the factors associated with optimism is culture. This study was conducted to examine the differences of optimism given various ethnicities on midwifery students. The study sample was the 476 vocational students majoring in midwifery that were located in the provinces of DKI Jakarta, West Java, Banten, and West Sumatra (women only, age ranged 19-20 years). The LOT-R questionnaire was used to collect data on optimism. The results of One-Way ANOVA test showed that there was no significant difference on optimism in view of ethnicity (F=1.040; p>.05). The future studies should involve more participants from various ethnicities in Indonesia, especially ethnicities in the eastern region of Indonesia.Â